Regional encounters: explaining the divergent responses to the EU's support for regional integration in Africa, the Caribbean and Pacific. Issue 4 (3rd July 2016) - Heron, Tony; Murray-Evans, Peg
Abstract: In this article, we map and explain the unevenness of African, Caribbean and Pacific (ACP) responses to the EU's external promotion of regional integration in the context of the Economic Partnership Agreements (EPAs). Although the controversies associated with the EPAs are typically attributed to a common set of problems, what remains to be fully explained is why these manifested themselves to a greater or lesser extent in different national and regional contexts. We account for this variance as a product of the degree of congruence between the institutional trajectory of individual regional projects and the model of economic integration prescribed by the EU in its post-Lomé prospectus for the ACP. We describe this congruence as either 'high', 'medium' or 'low' and use this explanatory model to account for variances in ACP responses to the EPAs, which would otherwise provide an untidy fit with accounts preoccupied with the economic determinants of bargaining outcomes.